Environmental novelty exacerbates stress hormones and Aβ pathology in an Alzheimer’s model - Kimberley E. Stuart (Nature Portfolio, 2017)
Abstract Cognitive stimulation has been proposed as a non-pharmacological intervention to be used in primary, secondary and tertiary prevention approaches for Alzheimer’s disease. A common familial Alzheimer’s disease transgenic model showed heightened levels of the stress hormone, corticosterone. When exposed to periodic enhanced cognitive stimulation, these animals demonstrated further heightened levels of corticosterone as well as increased Aβ pathology. Hence, Alzheimer’s disease may be associated with hypothalamic-pituitary-adrenal (HPA) axis dysfunction, causing stimulatory environments to become stress-inducing, leading to a glucocorticoid-pathology cycle contributing to further Aβ release and plaque formation. This finding suggests that stimulation-based interventions and local environments for people with Alzheimer’s disease need to be designed to minimise a stress response that may exacerbate brain pathology.